Differences and correlation analysis of feeding habits and intestinal microbiome in Schizopygopsis microcephalus and Ptychobarbus kaznakovi in the upper reaches of Yangtze River - Wang, Xinyu; Hao, Jiahui; Zhang, Cunfang; Zhu, Ping; Gao, Qiang; Liu, Dan; Nie, Miaomiao; Jia, Junmei; Qi, Delin (Frontiers in Microbiology, 2025)
BackgroundThe intestinal microbiota has co-evolved with the host to establish a stable and adaptive microbial community that is essential for maintaining host health and facilitating food digestion. Food selection is a critical factor influencing variations in gut microbial composition, shaping gut microbiome communities, and determining the ecological niches of fish.MethodsIn this study, high-throughput amplicon sequencing of 16S rRNA and 18S rRNA was utilized to compare the dietary and gut microbial differences between Schizopygopsis microcephalus and Ptychobarbus kaznakovi, both collected from the same sites in the Tuotuo River and Tongtian River, which are tributaries of the Yangtze River. We compared the microbial community structure, diet composition, and diversity between the two fish species using various analytical methods, including LefSe, α-diversity and β-diversity analyses. Additionally, we constructed co-occurrence networks to determine their correlations.Results and discussionThe alpha diversity results indicated that S. microcephalus exhibited higher intestinal microbiota and feeding diversity compared to P. kaznakovi. Furthermore, the beta diversity results revealed significant differences in both intestinal microbiota and eukaryotic communities between the two species. The dominant bacterial phyla in both S. microcephalus and P. kaznakovi included Proteobacteria, Firmicutes, Actinobacteriota, Chloroflexi, and Verrucomicrobiota; however, Firmicutes was significantly more abundant in P. kaznakovi (P = 0.006), while Actinobacteriota was significantly higher (P = 0.019) in S. microcephalus at the phylum level. The primary food sources for S. microcephalus and P. kaznakovi were identified as Streptophyta (54.41%, 77.50%) and Cercozoa (8.67%, 1.94%), with Bacillariophyta (25.65%) was also the main food of constituting a major component of the diet for S. microcephalus. These differences suggested that S. microcephalus and P. kaznakovi occupy distinct dietary niches. To further explore the relationship between gut microbiota and feeding habits, we identified significant correlations between various food components and the gut microbial community through co-occurrence networks. This study enhances our understanding of the co-evolution and co-adaptation between host gut microbiota and feeding behaviors in sympatric fish species.